Resonant control system for low‐voltage ride‐through in wind energy conversion systems. Issue 6 (1st May 2016) - Cárdenas, Roberto; Díaz, Matías; Rojas, Félix; Clare, Jon; Wheeler, Pat
Abstract : Owing to the high penetration of electrical energy from wind energy conversion systems (WECSs), some countries are enforcing stringent grid codes to regulate low‐voltage‐ride‐through (LVRT) operation of WECSs. This study presents a self‐tuning resonant control (RC) system which can be used for LVRT control of the grid interface in the presence of symmetrical or asymmetrical faults. Only two RCs are required to fully control the four degrees of freedom of the converter output current. Sequence component separation is achieved using a new fast‐convergence delayed signal cancellation method which is also discussed in this work. The mathematical analysis and design procedure of the control system are presented. Simulation and experimental results obtained from a 3 kW prototype are discussed in this study.